Ag-Data Hub Webinar with Senegal’s Agricultural Extension and Advisory Service Providers - Grossi, Amanda; Braun, Melody; Hansen, James; Trzaska, Sylwia; List, Geneva; Dhulipala, Ram; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A webinar on the topic of Senegal’s newly launched Ag-Data Hub was convened with Senegal’s main public and private agricultural extension and advisory service (EAS) providers on April 27, 2023. The webinar, which was organized as part of the World Bank’s Accelerating the Impacts of CGIAR Climate Research for Africa (AICCRA) project, brought together EAS providers who were involved in the co-production, training of trainers (ToT), and upcoming pilot of the newly developed Climate Risk Management in Agricultural Extension (CRMAE) curriculum to learn more about the Ag-Data Bub incorporated within the curriculum’s Module 2 covering climate information and tools available for agriculture in Senegal. The Ag-Data Hub integrates data from multiple sources to help farmers and those who support them such as EAS to make informed decisions such as about which crops or varieties to plant in a given location, when to sow them, and more.